Regulation of Gramicidin Channel Function Solely by Changes in Lipid Intrinsic Curvature - Maer, Andreia M.; Rusinova, Radda; Providence, Lyndon L.; Ingólfsson, Helgi I.; Collingwood, Shemille A.; Lundbæk, Jens A.; Andersen, Olaf S. (Frontiers in Physiology, 2022)
Membrane protein function is regulated by the lipid bilayer composition. In many cases the changes in function correlate with changes in the lipid intrinsic curvature (c0), and c0 is considered a determinant of protein function. Yet, water-soluble amphiphiles that cause either negative or positive changes in curvature have similar effects on membrane protein function, showing that changes in lipid bilayer properties other than c0 are important—and may be dominant. To further investigate the mechanisms underlying the bilayer regulation of protein function, we examined how maneuvers that alter phospholipid head groups effective “size”—and thereby c0—alter gramicidin (gA) channel function. Using dioleoylphospholipids and planar bilayers, we varied the head groups’ physical volume and the electrostatic repulsion among head groups (and thus their effective size). When 1,2-dioleyol-sn-glycero-3-phosphocholine (DOPC), was replaced by 1,2-dioleyol-sn-glycero-3-phosphoethanolamine (DOPE) with a smaller head group (causing a more negative c0), the channel lifetime (tau) is decreased. When the pH of the solution bathing a 1,2-dioleyol-sn-glycero-3-phosphoserine (DOPS) bilayer is decreased from 7 to 3 (causing decreased head group repulsion and a more negative c0), tau is decreased. When some DOPS head groups are replaced by zwitterionic head groups, tau is similarly decreased. These effects do not depend on the sign of the change in surface charge. In DOPE:DOPC (3:1) bilayers, pH changes from 5 to 9 and 5 to 0 (both increasing head group electrostatic repulsion, thereby causing a less negative c0) both increase tau Nor do the effects depend on the use of planar, hydrocarbon-containing bilayers, as similar changes were observed in hydrocarbon-free lipid vesicles. Altering the interactions among phospholipid head groups may alter also other bilayer properties such as thickness or elastic moduli. Such changes could be excluded using capacitance measurements and single channel measurements on gA channels of different lengths. We conclude that changes gA channel function caused by changes in head group effective size can be predicted from the expected changes in c0.